2019
DOI: 10.1021/acs.jpcc.8b10473
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Faradaic Reactions and Electrokinetic Phenomena at a Nanochannel-Confined Bipolar Electrode

Abstract: We present the most comprehensive two-dimensional numerical model to date for a nanoconfined bipolar electrochemical system. By accounting for the compact Stern layer and resolving the diffuse part of the electrical double layer at the bipolar electrode (BPE) surface and channel walls, our model captures the impact of surface polarization and ionic chargescreening effects on the heterogeneous charge-transfer kinetics, as well as nonlinear electrokinetic transport phenomena such as induced-charge electroosmosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 67 publications
1
17
0
Order By: Relevance
“…83 Specifically, the supporting CsF electrolyte (and F – source) could be used at concentrations of only 1 mM, whilst typically 100 mM or more supporting electrolyte is often required. Conducting a reaction in a low supporting electrolyte concentration such as this could provide alternative options in both organic synthesis and analysis 85…”
Section: Bipolar Electrochemistrymentioning
confidence: 99%
“…83 Specifically, the supporting CsF electrolyte (and F – source) could be used at concentrations of only 1 mM, whilst typically 100 mM or more supporting electrolyte is often required. Conducting a reaction in a low supporting electrolyte concentration such as this could provide alternative options in both organic synthesis and analysis 85…”
Section: Bipolar Electrochemistrymentioning
confidence: 99%
“…Pennathur and coworkers devised a series of experiments and computational models to study the charging and discharging behavior of a BPE confined within a nanochannel. 108,125,126 First, the authors modeled the charging of the BPE, the electrode polarization, charge transfer kinetics, and mass transport that occur under an applied potential. 125 Lastly, the group corroborated their experimental results by modeling the discharging behavior of a nano-confined BPE upon removal of an applied external electric field.…”
Section: Nanoscale Bipolar Electrochemistrymentioning
confidence: 99%
“…108,125,126 First, the authors modeled the charging of the BPE, the electrode polarization, charge transfer kinetics, and mass transport that occur under an applied potential. 125 Lastly, the group corroborated their experimental results by modeling the discharging behavior of a nano-confined BPE upon removal of an applied external electric field. 108 It was found that after the applied voltage is removed, the EDL continues to keep the BPE polarized, while counterions are attracted to the poles to re-establish neutrality.…”
Section: Nanoscale Bipolar Electrochemistrymentioning
confidence: 99%
“…29,30 Similar non-linear electrokinetic transport phenomena have also been reported by using isolated symmetrical sharp corners 31,32 or bipolar electrodes inside a straight microchannel. [33][34][35] Other approaches to transporting particles through or trapping them in/near pores use linear electro-osmotic effects in combination with a secondary driving mechanism. For example, Cevheri and Yoda 36,37 have reported that CPs were concentrated at the microchannel wall and form bands when the pressure driven flow opposes electro-osmotic flow.…”
Section: Electrically Driven Colloid Transportmentioning
confidence: 99%